The rise of behavior-cognitive therapies and it’s consequences for the development of a behavioralanalytic clinical approach of private events. (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
The paper discusses, from the viewpoint of the analysis of historical aspects, the birth of cognitivebehavioral therapies and their impact to the field of behavior analysis. Some factors that seem to relate to such birth may be: the lack of a greater conceptual development for a particular clinical approach for the concept of private events; the tradition of behavior modification with basic research with animals; and a greater interest on direct manipulation of environmental contingencies instead of intervention on the clients' thoughts and feelings. It is considered that a greater acception and spread of cognitive-behavioral therapies, since the 1970s, favored the rebirth of tradition concepts in psychology used to explain behavior, and on the other side, contributed to a greater concern of behavior analysts do respond to the frequent critics of cognitive-behavioral therapists to a supposal lack of behavioral therapies to approach complex human behavior, resulting on the rebirth of new therapeutical propositions, still consistent with the assumptions of radical behaviorism but able to deal with feelings and emotions in their practice.
Keywords: Behavioral-analytic therapy; Cognitive-behavior therapy; Private events